THE INFLUENCE OF PRODUCT QUALITY, PRODUCT DESIGN AND PRICE ON THE DECISION TO PURCHASE BOGO RETRO CLASSIC HELMETS AMONG MANAGEMENT STUDYPROGRAM STUDENTS FACULTY OF ECONOMICS AND BUSINESS MALIKUSSALEH UNIVERSITY - Uli Artha Manullang; T. Edyansyah; Adnan; Muchsin (RADJA PUBLIKA, 2024)
This research aims to see the influence of product quality, product design and price on purchasing decisions for Bogo Retro Classic helmets among students in the Management Study Program, Faculty of Economics and Business, Malikussaleh University. The sampling technique in this research is purposive sampling. The sample in this study was 92 consumers who used Bogo Retro Classic helmets among students in the Management Study Program, Faculty of Economics and Business, Malikussaleh University. The analytical tools used are multiple linear regression tests and hypothesis testing using the t test and F test. The results of the research show that partially the variables Product Quality and Product Design have a positive and insignificant influence on the decision to purchase Bogo Retro Classic helmets among students in the Management Study Program, Faculty of Economics. and Malikussaleh University Business. Meanwhile, the price variable has a significant influence on the decision to purchase the Bogo Retro Classic helmet for students in the Management Study Program, Faculty of Economics and Business, Malikussaleh University. The variables of product quality, product design and price have a positive and significant effect on the decision to purchase the Bogo Retro Classic helmet for students in the Management Study Program, Faculty of Economics and Business, Malikussaleh University.